THE ROLE OF FICTION BOOKS IN SHAPING THE HUMAN QUALITIES OF PRESCHOOLERS (Scientific journal of the Fergana State University, 2024)
This article shows the role and importance of fiction in the formation of human qualities of preschool children and the creation of a favorable educational environment for children.